Pengembangan Panduan Ekstrakurikuler Pramuka Penegak Berbasis Kearifan Lokal pada SMA dan SMK Kota Salatiga - Listiarum, Febri; Jati, Dionisius Heckie Puspoko; Ningtyas, Ruth Siwi (Cetta: Jurnal Ilmu Pendidikan, 2024)
The lack of appreciation among students at SMK Saraswati and SMA Kristen Satya Wacana in Salatiga towards instructors during lessons, coupled with the limited use of instructional materials (primarily textbooks), which are often solely held by educators and not accessible to students, prompted this research. This study aims to develop and evaluate a media-based Scout learning guide to enhance teaching effectiveness on Scout topics such as Scouting History, Morse Code, Semaphore, and Knotting. Currently, these topics lack sufficient media resources, leading to student difficulties in comprehending and mastering the material. This research employs the ADDIE model, comprising the stages of Analysis, Design, Development, Implementation, and Evaluation, to ensure a systematic and comprehensive development process. The instruments used include practicality questionnaires for Scout instructors and students, validation questionnaires from content and media experts, and tests assessing students' understanding of Scout topics. Validation results show that the guide received scores of 76% from media experts, 86% from content experts, and 74% from prospective users. Overall, the guide achieved an average score of 72% in terms of practicality and feasibility, indicating that it falls into the "highly suitable" category for use in secondary school settings. These findings suggest that the ADDIE model-based learning guide is not only feasible but also effective in helping students better understand Scout topics and fostering their interest in Scouting activities. Therefore, it can be concluded that developing media-based learning materials using the ADDIE model results in a guide that is both feasible and effective for use in secondary school Scout education.